QUO VADIS PENGATURAN DISKRESI PEMERINTAH PASCA UNDANG-UNDANG CIPTA KERJA - Lintang Ario Pambudi (LPPM Universitas Ekasakti Padang, 2023)
The government, in carrying out its duties as a public servant for the welfare of society, sometimes encounters various problems that must be resolved as soon as possible, but there is no legal regulation governing this matter. As a solution to this condition, government officials are given the authority to use discretion in the Government Administration Law. With the passing of the Job Creation Law, the concept of discretion changed which is regulated in the Government Administration Law. The problem is regarding how discretion is regulated after the Job Creation Law and whether this discretion can be used as an object of the lawsuit in the state administrative court. This research is a normative juridical research with a conceptual and statutory approach. The conclusion is that the concept of discretion in the Government Administration Law adheres to the concept of limited discretion, this has been changed by the Job Creation Law which adheres to the concept of discretion broadly by eliminating the requirement that discretion must comply with applicable laws and regulations. Even so, discretion as the object of a lawsuit in the state administrative court can still base a lawsuit that the discretion is contrary to statutory regulations. Suggestions for government officials using discretion must be careful and pay attention to the applicable laws and regulations.